The Correlation of Infection Prevention and Control Knowledge and ESBL Carriage Rate among Healthcare Workers in a Hospital in Indonesia - Fanani, Navalia Azkarifda; Krisniawati, Nia; Wicaksono, Madya Ardi; Hestiyani, Rani Afifah Nur; Widhi, Anriani Puspita Karunia Ning (Fakultas Kedokteran Universitas Brawijaya, 2025)
Extended-spectrum beta-lactamase (ESBL) is an enzyme resulting from bacterial gene mutations that can restrict the activity of beta-lactam antibiotics, such as penicillin, the first, second, and third generation of cephalosporin, and monobactam, except cephamycin and carbapenem. ESBL can cause healthcare-associated infections (HAIs). Infection prevention and control (IPC) is a comprehensive effort to prevent HAIs in healthcare facilities. This research investigated the correlation between IPC knowledge level and the incidence of extended-spectrum beta-lactamase (ESBL) producing bacteria carriers in hospital healthcare workers. This research was conducted as observational analytical research using the quantitative and cross-sectional approaches. The research used purposive sampling, involving 61 healthcare workers at Banjarnegara Islamic Hospital. Research instruments included a 24-item questionnaire assessing IPC knowledge and rectal swabs intended to detect the incidence of ESBL carriers using the CHROMagar™ ESBL medium. Most respondents have a relatively good understanding of IPC, with a median score of 16 (25%). Of the 61 rectal swab samples, eight incidences of ESBL carriers were identified (13%). The isolates of the recognized carriers consist of five Escherichia coli (63%), two Klebsiella pneumoniae (25%), and one Acinetobacter baumannii (12%). Statistical analysis using the Mann-Whitney hypothesis test with the SPSS software showed a significant value of 0.493. Therefore, there is no correlation between IPC knowledge level and the incidence of extended-spectrum beta-lactamase-producing bacteria carriers in hospital healthcare workers.